2014
DOI: 10.1016/j.jpaa.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The groups of automorphisms of the Lie algebras of triangular polynomial derivations

Abstract: The group of automorphisms Gn of the Lie algebra un of triangular polynomial derivations of the polynomial algebra Pn = K[x1, . . . , xn] is found (n ≥ 2), it is isomorphic to an iterated semi-direct productwhere T n is an algebraic n-dimensional torus, UAutK (Pn)n is an explicit factor group of the group UAutK (Pn) of triangular polynomial automorphisms, F ′ n and En are explicit groups that are isomorphic respectively to the groups I and J n−2 where I :It is shown that the adjoint group of automorphisms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
3

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 4 publications
0
12
0
3
Order By: Relevance
“…where T n is an algebraic n-dimensional torus, UAut K (P n ) n is an explicit factor group of the group UAut K (P n ) of unitriangular polynomial automorphisms, F ′ n and E n are explicit groups that are isomorphic respectively to the groups I and J n−2 where I := (1 + t 2 K[[t]], ·) ≃ K N and J := (tK[[t]], +) ≃ K N . It is shown that the adjoint group of automorphisms A(u n ) of the Lie algebra u n is equal to the group UAut K (P n ) n (Theorem 7.1, [5]). Recall that the adjoint group A(G) of a Lie algebra G is generated by the elements e ad(g) := i≥0…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where T n is an algebraic n-dimensional torus, UAut K (P n ) n is an explicit factor group of the group UAut K (P n ) of unitriangular polynomial automorphisms, F ′ n and E n are explicit groups that are isomorphic respectively to the groups I and J n−2 where I := (1 + t 2 K[[t]], ·) ≃ K N and J := (tK[[t]], +) ≃ K N . It is shown that the adjoint group of automorphisms A(u n ) of the Lie algebra u n is equal to the group UAut K (P n ) n (Theorem 7.1, [5]). Recall that the adjoint group A(G) of a Lie algebra G is generated by the elements e ad(g) := i≥0…”
Section: Introductionmentioning
confidence: 99%
“…By (Theorem 3.6. (2), [5]), there exists a unique automorphism σ ∈ T n ⋉ T n ⊆ G n such that σ(∂ i ) = ∂ ′ i for i = 1, . .…”
Section: Introductionmentioning
confidence: 99%
“…(8), we have the automorphism σ ′ ∈ Q n such that, by Lemma 2.12. (3,6), σ ′−1 σ ∈ Fix En (∂ 1 , . .…”
mentioning
confidence: 99%
“…Вводится новая размерность для алгебр и модулейоднорядная размерность (см. § 4), которая оказалась очень полезным инструментом в изучении ненётеровых алгебр Ли, их идеалов и автоморфизмов [1], [2]. В § 3 дается классификация всех идеалов алгебры u n и для каждого идеала указывается явный базис.…”
unclassified
“…В [1] найдены группа автоморфизмов Aut K (u n ) алгебры Ли u n и ее явные порождающие и показано, что присоединенная группа ⟨e ad(a) | a ∈ u n ⟩ является очень малой частью группы Aut K (u n ).…”
unclassified